The Characteristics of Deviated Nasal Septum Patients and Computed Tomography Findings at Dr. Mohammad Hoesin General Hospital Palembang - Ermalinda Kurnia; Fiona Widyasari; Puspa Zuleika; Ahmad Hifni; M Ricky Al Hafiz Sazili (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Introduction. The deviated nasal septum is found in 80% of people in the world either with or without specific symptoms. Mladina has divided the classification of deviation of the septum nasi into seven parts based on the findings of the deviation to facilitate the determination of diagnosis, therapy, and which type often appears. This study aims to determine the characteristics of patients with a deviated nasal septum at Dr. Mohammad Hoesin General Hospital Palembang from January to December 2021. Methods. Data was obtained from medical records of patients with a deviated nasal septum at Dr. Mohammad Hoesin General Hospital Palembang from January to December 2021. Results. The majority of patients were in the age range of 16-25 years (37.8%) and male gender (64.9%). The most common etiology was congenital (86.5%). Clinical manifestation mainly is nasal obstruction (94.6%), and the most common secondary diagnoses found are concha hypertrophy (54%) and allergic rhinitis (16.2%). The most common pathological condition was narrowed cavum nasal (91.9%). The majority of patients had type III deviation (51.4%). All patients were treated with septoplasty (100%). Conclusion. Most patients are predominantly male aged between 16-25 years. Congenital factors primarily caused this condition, leading to complaints of nasal obstruction. Secondary diagnoses included concha hypertrophy and allergic rhinitis. Physical examinations often revealed a narrowed nasal cavity. Most patients exhibited type III septal deviation and all patients were treated with septoplasty